2019
DOI: 10.1590/0102-311x00179318
|View full text |Cite
|
Sign up to set email alerts
|

Escala de Influência dos Três Fatores (TIS) aplicada a estudantes universitários: estudo de validação e aplicação

Abstract: Resumo: A Escala de Influência dos Três Fatores (TIS) é utilizada para avaliar a influência de aspectos sociais e familiares na aparência corporal dos indivíduos. Contudo, poucos indícios de validade de construto da TIS são apresentados. O objetivo do estudo foi estimar os indicadores psicométricos da TIS e identificar o grau de influência da mídia, pais e amigos na aparência corporal de universitários considerando diferentes características. Universitários de ambos os sexos participaram. Os indicadores psicom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…This corroborates the theory of the Tripartite Model, in which social pressure agents propagate the internalization of the ideal body according to the local culture. Previous studies 31,43,51,52,53,54 have confirmed this relationship between sociocultural factors and body image. In the Brazilian context, Carvalho et al 35 reported that only pressures from the family and the media had a significant relationship with the internalization of the ideal body in adult women.…”
Section: Discussionsupporting
confidence: 54%
“…This corroborates the theory of the Tripartite Model, in which social pressure agents propagate the internalization of the ideal body according to the local culture. Previous studies 31,43,51,52,53,54 have confirmed this relationship between sociocultural factors and body image. In the Brazilian context, Carvalho et al 35 reported that only pressures from the family and the media had a significant relationship with the internalization of the ideal body in adult women.…”
Section: Discussionsupporting
confidence: 54%
“…A study on the validation of the Three Factors Influence Scale applied to university students, used similar indices in the analysis (χ 2 /DoF = 2.97, RMSEA = 0.08, CFI = 0.87, TLI = 0.86), evidencing an adequate instrument to measure the construct (32).…”
Section: Discussionmentioning
confidence: 98%
“…Understanding the relevance of rules and values in each cultural or social context is crucial to recognizing internalization and body comparison in individuals (Silva et al, 2019;Stojcic et al, 2020;Thompson et al, 1999;van den Berg et al, 2002), hence the pertinence of performing transcultural studies (Strahan et al, 2006). While several studies have reported higher proportions of body image distortion in women from Western societies compared to those from non-Western societies (Makino et al, 2004;Schaefer et al, 2019), others have highlighted regional differences in body image even between populations of Western countries (Schaefer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%